2021
DOI: 10.1002/jmv.27464
|View full text |Cite
|
Sign up to set email alerts
|

Profiling serum levels of glutathione reductase and interleukin‐10 in positive and negative‐PCR COVID‐19 outpatients: A comparative study from southwestern Iran

Abstract: Since the outbreak of COVID‐19 in China, it has rapidly spread across many other countries. We evaluated antioxidant defense systems and inflammatory status related to the SARS‐CoV2 infection in a population from southwestern Iran. Comorbidities and clinical symptoms of 104 subjects (comprising negative and positive‐PCR COVID‐19 outpatients) were assessed. Serum concentrations of glutathione reductase (GR) and interleukin‐10 (IL‐10) were measured using ELISA. In the positive‐PCR group, follow‐ups on clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(48 reference statements)
0
7
1
Order By: Relevance
“…This enzyme is essential for the GSH regeneration. A study in 104 subjects showed that the activity of GR was decreased in the SARS-CoV-2 infection [25]. Our results show a decrease in the activity of this enzyme and, although there was a tendency of the activity of GR to increase due to treatment with NAC, it did not show a statistical difference.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This enzyme is essential for the GSH regeneration. A study in 104 subjects showed that the activity of GR was decreased in the SARS-CoV-2 infection [25]. Our results show a decrease in the activity of this enzyme and, although there was a tendency of the activity of GR to increase due to treatment with NAC, it did not show a statistical difference.…”
Section: Discussioncontrasting
confidence: 76%
“…The temperature median was of 36 , the arterial pressure (78, 71-102 mmHg), the body temperature (36, 36.5-37.2 • C), total cholesterol (1363, 89-210 mg/dL), triglycerides (186.5, 80-726 mg/dL), high-density lipoprotein (26, 14-40 mg/dL), low-density lipoprotein (62, 40-110 mg/dL), leukocytes (8.8, 3.5-14.9 10 3 /µL), lymphocytes (8.3, 0.14-1.54 10 3 /µL), platelets median (253, 164-408 10 3 /µL), ferritin (435.4, 146-2592 ng/mL), D-dimer (605, 200-2100 µg/mL), CRP (143.15, 44.7-221 mg/L), IL-6 (16, 7.8-324 pg/mL), NR (8.4, 6-67), procalcitonin (0.23, 0.08-11.4 ng/mL). The sepsis score according to SOFA index was (0, 0-3), APACHE (5.5, 4-8), and SAPS (27,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The patients with moderate and severe condition were 8, respectively (50/50%), and the number of days with mechanic ventilation was (13,, days in ICU were (17,, and death 2 (12%).…”
Section: Demographic Characteristics Of the Patients Infected By Sars...mentioning
confidence: 99%
“…There were 10 up-regulated enzymes responsible for the increased flux of related metabolic reactions, including pyruvate kinase M1/2 (PKM), cytidine/uridine monophosphate kinase 2 (CMPK2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), SLC38A5, SLC16A1, SLC2A3, glutathione-disulfide reductase (GSR), myeloperoxidase (MPO), cytochrome P450 family 1 subfamily B member 1 (CYP1B1), and galactosidase beta 1 (GLB1). As a known metabolic marker in serum, GSR shows a significant negative correlation with increased IL-10 in COVID-19 patients [ 85 ]. In addition, MPO involved in steroid metabolism is considered as a neutrophil-derived infection marker to activate the production of cytokines and ROS in severe SARS-CoV-2 infection [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms such as productive cough, dyspnea, and delirium are significantly associated with COVID-19 mortality, emphasizing the need for immediate monitoring and intervention [ 56 ]. Laboratory tests show altered hematologic and biochemical markers in deceased patients, underscoring the importance of routine laboratory monitoring in COVID-19 patients [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%